1964
DOI: 10.1002/pol.1964.100020217
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of polybutadienes prepared by n‐butyllithium initiation

Abstract: synopsisThe flow behavior of n-butyllithium-polymerized polybutadienee w a investigated aa a function of molecular weight, temperature, and shear rate. At low shear r a h these polymers exhibit Newtonian flow up to molecular weighte of several hundred thousand so that "zero shear" Newtonian viscosities can readily be determined without the risk of long extrapolation. Above 1O.OOO molecular weight the Newtonian viscosities obey the well-known 3.4 power dependence on weight-average molecular weight. The entangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

1966
1966
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…Early studies on randomly branched poly(vinyl acetate) (PVA) and polybutadiene (PB) indicated higher melt viscosity than linear polymers of the same M w at sufficient branch lengths M b above the characteristic molecular weight between entanglements M e [64][65][66][67]. Graessley et al [68][69][70] and Raju et al (71) observed viscosity enhancement over that of linear polymers of equivalent molecular size in star and comb polyisoprene (PI), polystyrene (PS) and hydrogenated polybutadiene (HPB).…”
Section: Model Polymersmentioning
confidence: 99%
“…Early studies on randomly branched poly(vinyl acetate) (PVA) and polybutadiene (PB) indicated higher melt viscosity than linear polymers of the same M w at sufficient branch lengths M b above the characteristic molecular weight between entanglements M e [64][65][66][67]. Graessley et al [68][69][70] and Raju et al (71) observed viscosity enhancement over that of linear polymers of equivalent molecular size in star and comb polyisoprene (PI), polystyrene (PS) and hydrogenated polybutadiene (HPB).…”
Section: Model Polymersmentioning
confidence: 99%
“…In conjunction with this point, it is pertinent to note that a small amount of branched material, in contradistinction to the claims of others [23,24], is formed during the polymerization of butadiene [22,56]. This appears to be due to the susceptibility of the vinyl group to attack by an organolithium.…”
Section: Polymerization Proceduresmentioning
confidence: 79%
“…At this temperature, at l~ast several days are necessary for complete conver- SIOn. The measurement of viscosity is a convenient mode of determining the molecular weight of polymers prepared by these homogeneous anionic polymerization techniques. Values for K and a for several polymer-solvent pairs have been published; polystyrene [13,14], poly-a-methylstyrene [17], polyisoprene [20,] and polybutadiene [23,24].…”
Section: Polymerization Proceduresmentioning
confidence: 99%
“…89 ,90 This deviation may be caused by systematic deviations in the M w measurements as a result of different calibration procedures, measuring technique, etc. The master curve relations used above seem to be less vulnerable to this kind of uncertainty if all data used are based on experimental results from the same source.…”
Section: Fracture Phenomenamentioning
confidence: 99%